T Regulatory Lymphocytes During MBTA Immunotherapy of Pancreatic Adenocarcinoma - Simmer, Isabel (Jihočeská univerzita, 2023)
The aim of this bachelor thesis is to summarize the current knowledge in the field of T regulatory lymphocytes in cancer research as well as during intratumoral MBTA immunotherapy. In addition, methods to detect and target T regulatory lymphocytes are suggested in order to improve MBTA immunotherapy.
T Regulatory Lymphocytes During MBTA Immunotherapy of Pancreatic Adenocarcinoma
Keywords: Regulatory T lymphocytes; MBTA immunotherapy; Tregs detection and elimination; Cancer; Regulatory T lymphocytes; MBTA immunotherapy; Tregs detection and elimination; Cancer